2012
DOI: 10.1111/jace.12113
|View full text |Cite
|
Sign up to set email alerts
|

Camber Evolution and Stress Development of Porous Ceramic Bilayers During Co‐Firing

Abstract: Camber evolution and stress development during co‐firing of asymmetric bilayer laminates, consisting of porous Ce0.9Gd0.1O1.95 gadolinium‐doped cerium oxide (CGO) and La0.85Sr0.15MnO3 lanthanum strontium manganate (LSM)‐CGO were investigated. Individual layer shrinkage was measured by optical dilatometer, and the uniaxial viscosities were determined as a function of layer density using a vertical sintering approach. The camber evolution in the bilayer laminates was recorded in situ during co‐firing and it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In the present work the shrinkage, final density and potential distortion of ceramic multilayer systems during the co-sintering process have been measured using optical dilatometry [23][24][25]. The densification and strain rate development of single green layers of a MgO extrusion mass and a dip-coating composition (after de-bindering) as function of sintering temperature are shown in Fig.…”
Section: Co-sintering Of Porous Mgo Support/dense Cgo Membrane Layermentioning
confidence: 97%
“…In the present work the shrinkage, final density and potential distortion of ceramic multilayer systems during the co-sintering process have been measured using optical dilatometry [23][24][25]. The densification and strain rate development of single green layers of a MgO extrusion mass and a dip-coating composition (after de-bindering) as function of sintering temperature are shown in Fig.…”
Section: Co-sintering Of Porous Mgo Support/dense Cgo Membrane Layermentioning
confidence: 97%
“…3, the single-phase LNO starts shrinking at~1000 C, indicating that the sintering temperature should be at least higher than 1000 C to initiate the consolidation of particles at the interface. The LNOeGDC composite with coarse GDC powder (specific surface area of 15 m 2 g À1 ) exhibits inferior sintering behavior compared to the single phase LNO, and the onset sintering temperature was found to be above 1100 C. The sintering behavior of the ceramic composite is quite complex compared to the single-phase materials and is strongly influenced by the secondary phase inclusions [67,68]. Retardation of densification of the LNO-coarse GDC composite compared to the LNO single phase could be explained by the hydrostatic tensile stress countering the natural sintering stress and geometrical constraints imposed by the large GDC particles [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the importance of the co-firing process of asymmetric porous/dense ceramic bilayers, first asymmetric CGO bi-layers with different combinations of support and membrane layers were produced by lamination. These bi-layers were then co-sintered at a defined isothermal sintering cycle at a final temperature of 1050° C. Previous work described the cofiring as a major challenge in the preparation of defect free asymmetric porous/dense CGO bilayers [6], [18]. The experiments demonstrated that defect free bi-layers could be produced by combination of individual layers of porous CGO supports (high graphite supports (HG-CGO) and low graphite (LG-CGO)) and membrane layers (Co-CGO and Fe-CGO) at an isothermal sintering temperature of 1050 °C and an holding time of 4hrs.…”
Section: Isothermal Sintering Of Cgo Supports In Asymmetric Cgo Bi-lamentioning
confidence: 99%
“…Alternatively, porosity may be introduced in the support structure by inhibiting the sintering activity of the ceramic by using a relatively coarse-grained powder (with particle size in the micron range). However, this can introduce a differential sintering shrinkage between the (coarse-grained) porous support and the fine-grained membrane layer which will result in stresses that cause defects in the bi-layer structure during the subsequent co-firing [18]. It is also a requirement that the support structure has sufficient porosity to ensure the infiltration of catalyst material into the region close to the support/membrane interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation